Electricity Generation from Solar Energy: A Contemporary Study Integrating Physical Applications and Islamic Sharia Guidelines (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Maintaining the natural environment and striking a balance when using its resources is one of the main goals of Islamic law. The Kingdom of Saudi Arabia has been a leader in the search for alternative energy sources in order to meet life's demands and attain economic progress. It is working hard to generate renewable energy, the majority of which is derived from solar radiation. The Almighty God spoke the truth when He declared: "And He has subjected to you the night and the day and the sun and the moon, and the stars are subjected by His command. Surely , in this are proofs for a people who understand." (An-Nahl, ( 12)) . Allah has created the sun obedient to humans, and people have realized this and sought to take use of it. It is an amazing energy source whose significance stems from its enormous potential, which may be applied wherever. When utilized in numerous fields, it is regarded as clean energy since it is a free and limitless fuel supply. As a result, it need to be researched and used since it is a valid goal, particularly given the limited supply of conventional energy sources. To participate The Kingdom has prioritized investing in the field of solar energy for electricity production, working to reduce gas emissions, and paying attention to developing renewable energy sources, the most important of which is solar energy, which is something that Sharia calls for and urges, in order to achieve the goals of the Kingdom's Vision 2030 in diversifying the economy and transforming the Kingdom from an advanced oil-exporting country to an exporter of sustainable energy. The Kingdom of Saudi Arabia is blessed by God with an abundance of solar radiation in the Arab world. The intensity of solar radiation in the Arab region reaches 1000 watts/square meter at midday and an average of 250 to 300 watts/square meter per day, which is equivalent to 6 kilowatt-hours/square meter per day. Additionally, the Kingdom receives approximately 2200 kilowatts of photovoltaic energy annually. The King Abdullah University of Science and Technology's solar power generation project, the solar village project, the National Initiative for the Production of Water and Electricity Using Solar Energy under the auspices of King Abdulaziz City for Science and Technology, and other initiatives have been proposed by the government to capitalize on this. We must overcome some obstacles in order for the Kingdom to profit from solar energy. In addition to encouraging research in solar energy and scientific exchange with other nations, the government has offered material and spiritual support. As we shall discuss the function of solar energy in sustainable development, its significance and components, and how to take advantage of it as a clean energy source, the significance of this research is clear. The benefits of employing solar cells as a source of energy will also be discussed, along with how photovoltaic cells can be used to generate power. All of this will be connected to the specific scientific miracles stated in the Holy Quran and the Prophetic Sunnah, which demand advancement and modernization. In order to promote and realize Vision 2030, which the beloved Kingdom has called for, this research closes by showcasing advancements in solar energy technologies and applications.